Published as part of the Special Issue in Honor of Dr. Dani Schultz, the 2025 Women in Chemistry Award Winner - Ralph, Emma K.; DeMuynck, Bethany M.; Nagib, David (Synthesis, 2026)
Esters are a common motif found in drug molecules, improving pharmacokinetics, membrane permeability, binding selectivity, and even taste of oral medicines. The two most common methods used to synthesize methyl esters entail (i) Fischer esterification with strong acid and methanol or (ii) alkylation by diazomethane (or a less explosive, silyl analogue). These harsh methods often lack functional group tolerance or chemo-selectivity. Thus, we have developed an Fe-mediated methyl esterification of carboxylic acids using dibromomethane (CH2Br2) as the methylating reagent. This method exhibits excellent functional group tolerance with mild and inexpensive reagents. Methylation occurs on a wide range of carboxylic acids with alkyl, benzyl, allyl, halide, and heteroatom substituents, as well as in the presence of complex drug molecules and privileged amino acid motifs. Robustness elucidation, initial rate measurements, and substituent probe experiments provide further insight into the mechanism of this esterification. In conclusion, we have developed a robust, mild, and simple methylation of carboxylic acids with high functional group tolerance that provides a diazo-free alternative to esterification of complex molecules.
Keywords: Iron catalysis; Esterification; Methylation; Diazo-free; Carbene